Design of cooling channel in hot stamping tool by heuristic approach - Mohd Fawzi, Zamri (2017)
Owing to the demand for reducing gas emissions, energy savings, and the production of safer vehicles, the development of Ultra High Strength Steel (UHSS) materials is non-trivial. To strengthen a UHSS material such as boron steel, it is required to undergo a number of processes namely, heating it via hot stamping at a certain temperature and time as well as cooling it through quenching. In the hot stamping process, a similar die is used as in the cold stamping process, but with additional cooling channels. The cooling channel systems are integrated into the die design to control the heat transfer rate for quenching process of hot blanks. During quenching process, an effective die design contributes towards the achievement of the optimum heat transfer rate and homogeneous temperature distribution on hot blanks. In this study, the parameters of the cooling channel design i.e. the diameter of cooling channel (CA), the pitch between cooling channel (CB), the cooling channel distance to tool surface (CC), and the cooling channel distance to wall tool (CD) are optimised for a flat and U-shape tool using heuristic method. The heuristic method is coupled with the thermal and static analysis of finite element analysis (FEA) via ANSYS to determine the optimum design of hot stamping cooling channels. The static analysis are performed to ensure that the tool is able to withstand the applied pressure, whilst the thermal analysis was carried out to ensure homogeneous temperature distribution. Each parameter of the cooling channels optimised and benchmarked with traditional Taguchi method. Then, hot stamping process experiment is conducted to get the temperature distribution of the blank product and tool. Next, the simulation results were compared with experimental works for validation purpose. The result of the temperature distributation between FEA and experiment expected error less than 20 %. It is found that the optimum design of the hot stamping tool with a high heat transfer and lower von Mises stress (VMS), the following parameters (previously defined as CA, CB, CC, CD in mm) are required (8,8,10) mm for the flat tool, (8,8,8,10) mm for the upper U-shape tool and (8,8,8,8) mm for the lower U-shape tool, respectively. It is also evident that the pattern of the temperature distribution of the FEA model agrees the experimental results. Based on the flat shape tool, the average percentage error for the blank heat distribution is 1.83 % and for the tool is 2.67 %. As for the U-shape tool, the average percentage error for the upper tool, lower tool, and the blank heat distribution are 16.65 % 17.95 % and 7.92 %, respectively. The tensile strength and the hardness value of the blank products (flat and U-shaped samples) are measured to be approximately 1200 MPa and 600 HV, respectively. In conclusion, based on the aforementioned optimised parameters in the study, it is apparent that a high tensile strength with high value of hardness product could be produced from the heuristic method.